2010
DOI: 10.1002/cncr.25276
|View full text |Cite
|
Sign up to set email alerts
|

African ancestry and higher prevalence of triple‐negative breast cancer

Abstract: BACKGROUND The study of breast cancer in women with African ancestry offers the promise of identifying markers for risk assessment and treatment of triple-negative disease. METHODS African American and white American women with invasive cancer diagnosed at the Henry Ford Health System comprised the primary study population, and Ghanaian patients diagnosed and/or treated at the Komfo Anokye Teaching Hospital in Kumasi, Ghana constituted the comparison group. Formalin-fixed, paraffin-embedded specimens were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
168
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 33 publications
22
168
6
Order By: Relevance
“…Breast cancer in African women tend to be the ag- gressive triple negative subtype, [24] [36] similar to those observed in African-American women in the US, and is non-responsive to commonly used therapeutic drugs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Breast cancer in African women tend to be the ag- gressive triple negative subtype, [24] [36] similar to those observed in African-American women in the US, and is non-responsive to commonly used therapeutic drugs.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a study has shown that Ghanaian women are more likely to be diagnosed with high-grade tumors that are triple negative breast tumor [24]. Explanations for the delayed presentation among Ghanaian women have been traced to the cost of, and access to, routine screening mammography, lack of awareness, and cultural attitudes [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple negative breast cancer is significantly higher in African American women than all other ethnicities (138,139).…”
Section: Differences In Cancer Incidence and Mortalitymentioning
confidence: 93%
“…Even in an international study involving women of African ancestry, the racial disparity persisted (Stark et al, 2010). Premenopausal women tend to be at greatest risk of developing TNBC and up to 39% of all African American premenopausal women have TNBC (Carey et al, 2006).…”
Section: Race and Ethnicitymentioning
confidence: 99%